Treatment-failure to direct antiviral HCV regimens in real world: frequency, patient characteristics and rescue therapy - data from the German hepatitis C registry (DHC-R) = Therapieversagen nach direkt antiviraler HCV-Therapie in Real-world : Häufigkeit, Patientencharakteristika und Rescue-Therapie–Daten aus dem Deutschen Hepatitis C-Register (DHC-R) - Schmitt, Annika; Günther, Rainer; Mauss, Stefan; Böker, Klaus H. W.; Buggisch, Peter; Hillenbrand, Heribert; John, Christine; Klinker, Hartwig; Pathil-Warth, Anita; Simon, Karl-Georg; Serfert, Yvonne; Niederau, Claus; et al. (Zeitschrift für Gastroenterologie, 2020)
Background Virologic failure to approved combinations of direct antiviral agents (DAA) in patients with chronic hepatitis C virus (HCV) infection is rare. Mostly it involves difficult to treat patients with advanced liver disease and prior interferon-experience. Before approval of VOX/VEL/SOF, a restricted number of patients received rescue treatment, and the choice of DAA combinations for re-treatment were selected on an individual basis. In the present analysis, patient characteristics and rescue-regimens after virologic failure mainly based on first generation DAAs are described. Patients and methods Data were obtained from the German Hepatitis C-Registry (DHC-R), which is a national multicenter real-world cohort currently including about 16 500 patients recruited by more than 250 centers. The present analysis is based on 6683 patients who initiated a DAA therapy and for whom follow-up data (per-protocol analysis) were available. Results Among the patients, 188 (2.8 %) experienced a virologic relapse. Compared to SVR-patients, relapse patients were significantly more often male (77.7 % versus 56.9 %, respectively, p < 0.001), showed cirrhosis significantly more (48.4 % versus 28.1 %, respectively, p < 0.001) and a prior interferon-containing therapy (46.3 % versus 39.0 %, respectively, p = 0.049). The majority of patients who relapsed were infected with genotype 1 (47.4 %) followed by genotype 3 (29.8 %), and 95 relapse patients started DAA re-treatment. Characteristics of patients with rescue-treatment are similar to these of patients with relapse after initial DAA treatment. Thirty-one of 39 patients with complete follow-up data achieved SVR (79.5 %), and 8 patients had a relapse again (20.5 %). Patients who received rescue treatment including a new DAA class according to guidelines, except patients who received VOX/VEL/SOF, showed higher SVR rates than the entire group (21/25, 84 %). All patients who received VOX/VEL/SOF achieved SVR (n = 4, 100 %). Conclusions Patients with failure with DAA combination therapies are a difficult but urgent to treat population with the frequent presence of cirrhosis and prior treatment failure with interferon-based therapies. Rescue therapy with inclusion of a new DAA class leads to high SVR rates, but multiple targeted therapy with VOX/VEL/SOF seems to be most effective.